2014
DOI: 10.1128/jcm.00931-14
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Variation between Campylobacter jejuni Isolates Associated with Milk-Borne-Disease Outbreaks

Abstract: bBacterial genome sequencing has led to the development of new approaches for the analysis of food-borne epidemics and the exploration of the relatedness of outbreak-associated isolates and their separation from nonassociated isolates. Using Illumina technology, we sequenced a total of six isolates (two from patients, two from raw bulk milk, and two from dairy cattle) associated with a milk-borne Campylobacter jejuni outbreak in a farming family and compared their genomes. These isolates had identical pulsed-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…This work has clearly shown that, regardless of the methodology used, the genomic diversity among epidemiologically linked isolates within an outbreak investigation is limited to a few changes, which mainly affect homopolymeric runs. Revez et al, analyzing a milk-borne outbreak, observed up to 3 SNVs and phase variations in 12 loci between the milk-and patient-derived isolates, using a PubMLST-hosted whole-genome multilocus sequence typing (wgMLST) schema featuring 1,738 loci (15). A similar number of genomic differences (3 SNVs) was observed between one human isolate and the assumed source isolate in a waterborne outbreak (7).…”
Section: Application Of Wgs Of C Jejuni In Point-source Outbreak Invmentioning
confidence: 94%
See 1 more Smart Citation
“…This work has clearly shown that, regardless of the methodology used, the genomic diversity among epidemiologically linked isolates within an outbreak investigation is limited to a few changes, which mainly affect homopolymeric runs. Revez et al, analyzing a milk-borne outbreak, observed up to 3 SNVs and phase variations in 12 loci between the milk-and patient-derived isolates, using a PubMLST-hosted whole-genome multilocus sequence typing (wgMLST) schema featuring 1,738 loci (15). A similar number of genomic differences (3 SNVs) was observed between one human isolate and the assumed source isolate in a waterborne outbreak (7).…”
Section: Application Of Wgs Of C Jejuni In Point-source Outbreak Invmentioning
confidence: 94%
“…Due to their intrinsic genetic instability, variations observed in these genomic regions cannot be used to infer epidemiological relationships between isolates. Therefore, to ensure that the genetic signals used for tracing and source attribution of isolates are independent of genomic changes introduced by the host, such homopolymeric tracts should be excluded from genome comparisons in the context of public health investigations (7,8,15,16).…”
Section: Genomic Diversity During C Jejuni Infection and Colonizationmentioning
confidence: 99%
“…Recently, whole genome sequencing has offered that discriminatory power with the potential to enhance epidemiological investigations and elucidate transmission pathways (Phillips et al, 2016). The use of next-generation sequencing technology for WGS allows for the sequencing of large numbers of isolates, and novel bioinformatics tools can be used for comparative genomics and analysis of the phylogeny of the isolates (Revez et al, 2014). WGS has been a very useful and powerful tool for establishing potential links between clinical, food and environmental isolates of pathogens, which could allow the identification of the source of contamination and remove contaminated foods from markets (Deng et al, 2016).…”
Section: Whole Genome Sequencingmentioning
confidence: 99%
“…The cgMLST methods address this problem by comparing only genes common to a set of bacterial isolates (2). These methods are now mature and have been applied successfully to the analysis of a number of bacterial outbreaks (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).Given the developments in WGS-based strain typing described above, there is much excitement about applying these methods to real-time hospital epidemiology, but the actual cost-benefit equation, the feasibility of achieving results on an actionable time scale, and the technical requirements for implementation in a "real world" clinical microbiology laboratory are difficult to study. In work published in this issue of the Journal of Clinical Microbiology, …”
mentioning
confidence: 99%
“…The cgMLST methods address this problem by comparing only genes common to a set of bacterial isolates (2). These methods are now mature and have been applied successfully to the analysis of a number of bacterial outbreaks (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%